Racial/ethnic disparities in the prevalence and awareness of Hepatitis B virus infection and immunity in the United States - Kim, Hyun-seok (J Viral Hepat, 2017)
Hepatitis B virus (HBV) infection in the US is the most common among Asians followed by non-Hispanic blacks. However, there have been few studies that describe HBV infection and immunity by racial group. Our study aims to assess racial/ethnic disparities in the prevalence and awareness of HBV infection and immunity using nationally representative data. In the National Health and Nutrition Examination Survey 2011–2014, 14,722 persons had HBV serology testing. We estimated the prevalence of HBV infection, past exposure, and immunity by selected characteristics and calculated adjusted odds ratios using survey-weighted generalized logistic regression. Awareness of infection and vaccination history was also investigated. The overall prevalence of chronic HBV infection, past exposure, and vaccine-induced immunity was 0.34% [95%CI 0.24–0.43], 4.30% [95%CI 3.80–4.81], and 24.4% [95%CI 23.4–25.4], respectively. The prevalence of chronic infection was 2.74% [95% CI 1.72–3.76] in Asians, 0.64% [95% CI 0.35–0.92] in non-Hispanic blacks, and 0.15% [95% CI 0.06–0.24] in non-Asian, non-blacks. Only 26.2% of those with chronic infection were aware of their infection. The prevalence of the past exposure was 21.5% [95%CI 19.3–23.7] in Asians, 8.92% [95%CI 7.84–9.99] in non-Hispanic blacks, 2.05% [95%CI 1.49–2.63] in non-Hispanic whites, and 4.47% [95%CI 3.25–5.70] in Hispanics. Prevalence of vaccine-induced immunity by each race was 34.1% [95%CI: 32.0–36.2] in Asians, 25.5% [95%CI: 24.0–27.0] in non-Hispanic blacks, 24.0% [95%CI: 22.6–25.4] in non-Hispanic whites, and 22.2% [95%CI: 21.3–23.3] in Hispanics. There are considerable racial/ethnic disparities in HBV infection, exposure, and immunity. More active and sophisticated healthcare policies on HBV management may be warranted.